Symposium 5: International Tutor Perspectives on Undergraduate Networked Learning Environments: Symposium Introduction - Parchoma, Gale (Proceedings of the International Conference on Networked Learning, 2010)
Understanding selective adoption of specific models for technologically mediated learning environments (TMLEs), as well as the groups that form and adapt these environments—interact with and through them, and re-form the technologies within them—can begin with an examination of what makes theoretical constructs underpinning specific TMLEs desirable and/or adaptable. Desirability is an overtly subjective term, which can be related to preferred epistemological or pedagogical stances. Adaptability can be defined as the resilience of a desired TMLE—in this case, networked learning—in new places and cultures. To what degree can networked learning environments remain epistemologically and ontologically resilient across varied contexts? This view of adaptability affords the possibility that degrees of resilience are tentative: the ‘same’ design for a TMLE tailored for one teaching and learning setting, implemented in a new context, may become ‘wild’ (Engeström, 2009) or ‘different’ (Parchoma, in press). As academic disciplines can be defined as cultural settings marked by shared “practices, meanings, and discourse” (Mützel, 2009, p. 872), a networked learning environment, conceptualised for use in one or one group of disciplinary settings, may become either wild or different but still resist—in variant degrees—becoming either epistemologically or ontologically compromised or expanded in new geo-cultural or disciplinary contexts. This symposium brings together a collection of papers where we examine an international group of tutors’ perspectives on designing undergraduate networked learning environments and teaching through these environments. Empirical and theoretical investigations, grounded in this group of tutors’ stories from the field in Wales, Canada, Sweden, and Greece, are included. All of these papers are co-authored by student-tutor groupings of members of the e-Research and Technology Enhanced Learning doctoral programme based in Lancaster University. Each of the papers focuses on how ideas from selected networked learning literature, which originated primarily in UK and EU investigations into postgraduate teaching and learning settings, have come to influence this group of tutors’ designs for and experiences of teaching in undergraduate networked learning environments across a variety of national settings. Networked learning-specific conceptualisations of collaborative learning and assessment models are critically examined through this sample of implementations across a range of geo-cultural and disciplinary settings. Bell, Zenios, and Parchoma examine the challenges that campus based undergraduate students’ in a Welsh university experienced in moving from familiar face-to-face exchanges of voiced reflections on their learning into a networked learning environment where text based asynchronous discussion forms were the predominant form of communication. This empirical paper reports the findings of a small-scale action research study of the processes and actions of the learners as they reflected on their experiences of conducting fieldwork for a research methods course. The paper discusses how the learners grappled with collaboration in the online learning environment, describes the coping strategies they adopted, and questions the efficacy of relying upon written communications in networked learning environments. Bonzo and Parchoma explore paradoxes between institutional and student expectations for using social media to support learning in an undergraduate distributed medical education programme in Canada. This theoretical paper examines principles of social media, and how those principles relate to social constructivist approaches to teaching and learning. Three points of potential conflict between social and academic criteria for authentic knowledge construction in a networked learning environment are identified and explored. Oberg, Zenios, and Parchoma report a small scale study of Swedish tutors’ perceptions of and approaches to assessment in online undergraduate programmes. The paper opens with a literature review on trends to move from traditional multiple-choice, essay question exams, formal papers and scientific reports toward alternative methods which follow constructivist ideas, such as the integration of assessment into teaching and learning. While all participants in this study had training in the use of peer-assessment, the study findings indicated that peer-assessment was primarily used for formative assessment. Participants reported that large classes in undergraduate courses can lead to more traditional testing as a means of assessment. A major reason given by the teachers is also that students need to know about the subject area in more depth before being given responsibility over assessment. Being gradually acculturated and assimilated into the research community in the form of an apprenticeship is part of that process. All participants, in one way or another, conformed to the notion that students need to be ‘taught’ in their subject before being trusted with assessing their work. The essence of these findings is not to point out but to direct towards a new horizon. Through showing one interpretation and understanding of teachers’ perceptions of assessment, readers can meet the researcher’s interpretation of study data and then follow their own path forward toward comparing the outcome with the tenants of networked learning. Themelis, Parchoma, and Reynolds’ theoretical paper explores classical Athenian democracy as a conceptual framework for participatory learning and design in undergraduate networked learning communities. The authors examine the social structures and policies of classical Athenian democracy for potential insights into the design of networked learning communities. Structures and policies, including the ephebes and the power of reward, are interpreted in ancient and digital eras. Networked learning discussion forums, e-community managers, and tutors’ roles are examined under the lens of classical Athenian democratic ideals. Symposium presentations will briefly highlight ideas and issues around international, intercultural tutor experiences of designing networked learning environments and teaching undergraduate programmes in international contexts. Given the degrees of wildness or difference networked learning communities may acquire through translation into new geo-cultural or disciplinary contexts, questions on the extent to which they can or do honour the basic tenants of networked learning community theory remain open. If they cannot or do not retain networked learning principals, is networked learning community theory in-practice becoming compromised or expanded via implementations in new geo-cultural or disciplinary settings? Sufficient time for delegates to engage in a critical debate with symposium presenters will be provided.